Crime, Justice & the COVID-19 Pandemic: Toward a National Research Agenda - Miller, J. Mitchell (American journal of criminal justice, 2020)
The novel corona virus COVID-19 has become a worldwide public health pandemic that has induced anomic conditions impacting daily routines. COVID-19 response measures specifically alter regular schedules and both restrict and expand opportunities for various types of crime while presenting unprecedented challenges for the criminal justice system. For criminologists and criminal justice scientists, the virus also presents natural experiment conditions allowing for real-world theory tests and observation of the relative effectiveness of practice and policy options under weighty conditions. Toward synthesizing scientific discourse and forthcoming empirical work, we suggest the benefits of a COVID-19 crime and justice research program and offer some anchoring concepts. Contagion, containment measures (social distancing, facemasks, shelter-in-place, economic shutdown, virtual work and schooling, banned group gatherings), and social ordinance compliance (voluntary or enforced) posture a conceptual framework from which to align research on crime, justice, and victimization during the virus. After observing crime trends and justice system challenges, we suggest how the pandemic presents opportunities for review of various criminal justice, especially incarceration, policies. System change is a recurring theme across this special issue of the American Journal of Criminal Justice that features twenty additional contributions from a wide range of authoritative crime and justice scholars. These articles on traditional crime during the virus, virus specific hate crime and domestic violence, and the challenges posed by COVID-19 to law enforcement, the courts, and corrections will hopefully provide initial commentary toward deeper inquiry.